Criminal law - Samaha, Joel. (New York, 1987)
Teaching criminal law to undergraduates for twelve years has given me strong ideas about how to teach the subject. It has also generated clear views about what a good textbook ought to include.
Keywords: Criminal law -United States -Cases.